2018
DOI: 10.1111/jon.12509
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Hippocampal Inversion and Its Relationship to Hippocampal Subfield Volumes and Aging

Abstract: The rates of IHI prevalence in the current cohort are similar to those previously reported in healthy cohorts. The IHI severity is related to hippocampal subfield volumes, most notably the CA1, which is a novel finding with potential implications in research on aging and dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
4
11
0
Order By: Relevance
“…This work is ongoing and will serve as the basis for new validation experiments within the MRI domain (Olsen et al, 2019). The influence of incomplete hippocampal inversion -a common, atypical rotation of the hippocampal formation (Cury et al, 2015) that impacts subfield volumes (Colenutt et al, 2018) -presents another challenge.…”
Section: Summary Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…This work is ongoing and will serve as the basis for new validation experiments within the MRI domain (Olsen et al, 2019). The influence of incomplete hippocampal inversion -a common, atypical rotation of the hippocampal formation (Cury et al, 2015) that impacts subfield volumes (Colenutt et al, 2018) -presents another challenge.…”
Section: Summary Discussion and Outlookmentioning
confidence: 99%
“…Following this logic, most subjects in this category do not need to be excluded. Research on the effect of known normal variants is ongoing; more recently, a correlation between CA1 volumes and incomplete hippocampal inversion (IHI), a very common normal variant found in about 20% of healthy subjects (Colenutt et al, 2018), has been reported.…”
Section: Theoretical Considerations For Qcmentioning
confidence: 99%
“…Recently, Cury et al established a clear set of quantitative IHI criteria in a large healthy cohort [20]. Subsequent studies using these criteria reported consistent prevalence estimates and findings [36,37]. Employing the Cury criteria, the prevalence of IHI can now be reliably assessed in neuropsychiatric disorders such as schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the hippocampal volumes of participants with IHI did not differ from those without the variant. In a second study analyzing a healthy, aging cohort, the authors reported that participants with IHI do not differ in whole hippocampal volume, but show decreased subfield volumes, namely CA1 [37]. However, IHI lowers the accuracy of automated segmentation protocols, making it difficult to assess the effect of IHI on subfield volume estimates [39].…”
Section: Introductionmentioning
confidence: 99%
“…IHIs are mainly left-sided and characterized by a rounded or vertical shape, a medial positioning and a deep collateral sulcus [13][14][15] and are present in around 20% of the normal population [15]. It has been reported that IHI impacts the hippocampal volume: subjects with incomplete inversions appear to have smaller hippocampi [16], and more specifically, the hippocampal subfield CA1 seems to be related to the IHI severity [17]. Also it has been suggested that IHI might interfere with the quality of hippocampal segmentation for volumetric analysis [16,18], which may be clinically relevant, since the hippocampal volume can predict the response to antidepressant in patients without IHI [4,5].…”
Section: Introductionmentioning
confidence: 99%